2018
DOI: 10.1016/j.chemosphere.2017.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Persistence behavior of metamifop and its metabolite in rice ecosystem

Abstract: A field experiment was conducted to determine the persistence of metamifop in transplanted rice crop for two seasons. Metamifop 10% EC was applied at two doses: 100 g a.i. ha and 200 g a.i. ha at 2-3 leaf stage of Echinochloa crusgalli. The residues of metamifop along with its major metabolite, N-(2-fluorophenyl)-2-hydroxy-N-methylpropionamide (HFMPA), were estimated in rice plant, field water and soil using Liquid Chromatography Mass Spectrometry. Limit of detection and limit of quantification of the method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Metamifop can be quickly degraded to several metabolites in plants, including N-(2-fluorophenyl)-2-(4-hydroxyphenoxy)-Nmethylpropionamide (HPPFMA), HPFMA, 4-(6-chlorobenzooxazol-2-yloxy)phenol (CBOP), and 6-chloro-3H-benzooxazol-2-one (6-CBO) (Figure 4A). [45][46][47] In this study, metamifop and its major metabolites, HPFMA and 6-CBO, were identified by LC-MS/MS with retention times of 1.22, 0.76, and 0.77 min, respectively (Figure 4B-D). However, 6-CBO could not be quantified absolutely.…”
Section: Metamifop Metabolism In S and R Plants Of E Glabrescensmentioning
confidence: 73%
See 1 more Smart Citation
“…Metamifop can be quickly degraded to several metabolites in plants, including N-(2-fluorophenyl)-2-(4-hydroxyphenoxy)-Nmethylpropionamide (HPPFMA), HPFMA, 4-(6-chlorobenzooxazol-2-yloxy)phenol (CBOP), and 6-chloro-3H-benzooxazol-2-one (6-CBO) (Figure 4A). [45][46][47] In this study, metamifop and its major metabolites, HPFMA and 6-CBO, were identified by LC-MS/MS with retention times of 1.22, 0.76, and 0.77 min, respectively (Figure 4B-D). However, 6-CBO could not be quantified absolutely.…”
Section: Metamifop Metabolism In S and R Plants Of E Glabrescensmentioning
confidence: 73%
“…As documented, metamifop can be rapidly degraded to HPPFMA, HPFMA, CBOP, 6-CBO, and several other metabolites, and HPPFMA and CBOP will be degraded further to yield HPFMA and 6-CBO, respectively (Figure 4A). 45,46 In this study, the amounts of metamifop and its major metabolites HPFMA and 6-CBO were each compared between the S and R plants at different times after herbicide treatment. Unexpectedly, no significant difference in the amount of metamifop was revealed between the two biotypes at each time point.…”
Section: Discussionmentioning
confidence: 99%
“…By taking the logarithm (ln) in each side of the equation, this can be re-written as ln C t = ln C 0 − kt . The half-life ( t 1/2 ) value of flucetosulfuron can be calculated as: t 1/2 = ln 2/ k [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The major metabolite N ‐(2‐fluorophenyl)‐2‐hydroxy‐ N ‐methyl‐propionamide of metamifop in E. crus‐galli has been detected using liquid chromatography mass spectrometry (LC–MS) . This hints at the hydrolysis stability of the N ‐methyl‐propionamide fragment in the molecule in comparison with methyl ester cleavage (Fig.…”
Section: Chiral Herbicidesmentioning
confidence: 99%